STYLISTIC CONNOTATION IN ENGLISH - Ergasheva Nilufar Usar qizi (American Journals, 2022)
This article provides information about the styles of speech in English, the concept of connotation, stylistic connotation in English.
Keywords: Stylistic, connotation, experiential, style, speech, emotional, stylistic tool, standard